Petroleum Contaminated Soils : - Kostecki, Paul T. (Lewis, 1988)
These three volumes provide valuable information to help bring rational and scientifically feasible solutions to petroleum contaminated soils. State-of-the-art information on both technical and regulatory issues is covered, including environmental fate, health effects, risk assessment and remedial alternatives. They show why petroleum contaminated soils are a problem - and propose solutions for that problem. These books are an excellent reference for regulatory personnel and environmental consultants at all levels.